Design of fractional conversion ratio SC DC-DC converters - Pongswatd, Sawai; Smerpituk, Krit; Julsereewong, Prasit; Eguchi, Kei; Sasaki, Hirofumi (My University, 2013)
This paper presents the switched-capacitor (SC) circuit structure whose design conversion ratio is fraction multiple. The proposed converters can step up or step down the input voltage and bidirectional power flow by using dual converters connected. The 2x and 1/2x fraction conversion ratio is specified as a case study. The characteristics of the proposed converters are clarified by theoretical analyses. In addition, the simulation and experimental show the validity of circuit design, where theoretical results correspond well with simulation and experimental results. The proposed converters will be useful for battery charger, battery equalizer and dc power transfer. © 2013 IEEE.
Keywords: battery equalizer; DC-DC Converter; dual converter; Fractional conversion ratio; power transfer; Switched-Capacitor